2020
DOI: 10.3390/pharmaceutics12080724
|View full text |Cite
|
Sign up to set email alerts
|

π-Donor/π-Acceptor Interactions for the Encapsulation of Neurotransmitters on Functionalized Polysilicon-Based Microparticles

Abstract: Bipyridinium salts, commonly known as viologens, are π-acceptor molecules that strongly interact with π-donor compounds, such as porphyrins or amino acids, leading their self-assembling. These properties have promoted us to functionalize polysilicon microparticles with bipyridinium salts for the encapsulation and release of π-donor compounds such as catecholamines and indolamines. In this work, the synthesis and characterization of four gemini-type amphiphilic bipyridinium salts (1·4PF6–4·4PF6), and their immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, it has been previously demonstrated that gemini-cationic amphiphiles can self-assemble, forming micelles, 26 stabilizing gold nanoparticles, 27−29 or coating silicon microparticles. 30 Moreover, imidazolium-based amphiphiles such as 1•2Br act as low-molecular-weight gelators (LMWGs) in solvents of different nature, from organic solvents to ionic liquids. 31 They can form nanostructured supramolecular hydrogels for applications that span from topical drug delivery 32 to an enhanced efficiency of photosensitizers, 33 3D printing of polymeric hydrogels, 34 construction of lightcontrolled molecular machines, 35 and antibacterial hydrogels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been previously demonstrated that gemini-cationic amphiphiles can self-assemble, forming micelles, 26 stabilizing gold nanoparticles, 27−29 or coating silicon microparticles. 30 Moreover, imidazolium-based amphiphiles such as 1•2Br act as low-molecular-weight gelators (LMWGs) in solvents of different nature, from organic solvents to ionic liquids. 31 They can form nanostructured supramolecular hydrogels for applications that span from topical drug delivery 32 to an enhanced efficiency of photosensitizers, 33 3D printing of polymeric hydrogels, 34 construction of lightcontrolled molecular machines, 35 and antibacterial hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been previously demonstrated that gemini-cationic amphiphiles can self-assemble, forming micelles, stabilizing gold nanoparticles, or coating silicon microparticles . Moreover, imidazolium-based amphiphiles such as 1·2Br act as low-molecular-weight gelators (LMWGs) in solvents of different nature, from organic solvents to ionic liquids .…”
Section: Introductionmentioning
confidence: 99%